Relação entre o Conceito de Nova Gestão Pública do Centro Latino-Americano de Administração para o Desenvolvimento (CLAD) e as Políticas de Avaliação no Brasil. - Dorne, Fernanda Cristina Zimmermann (2020)
The objective of this dissertation is to analyze the relationship between the concept of The New Public Management of the Latin American Center for Development Administration (CLAD) and the policies for large-scale evaluation, structured in Brazil. The hypothesis is that the largescale evaluation in the country converges with the managerial orientations of CLAD. For this purpose, a qualitative approach was used, and the methodology was guided in a documental and bibliographic study about the international macro policy and its repercussion on the national policy. This study was organized on three main points. The first chapter presents an analysis of the historical conjuncture, policy, and ideology of the New Public Management and how it was triggered in the CLAD policies. Thus, it's evident how the concepts of the New Public Management were incorporated in the Brazilian policy, with the elaboration of the Master Plan for the Reform of the State System (PDRAE). The neoliberal interferences about the execution of this document contributed to the Reform of the State, and its organization in the managerial administration with the words of order: Evaluation State, citizen-client, meritocracy, penalization, and administrative accountability. From a market perspective, these principles have been incorporated in all sectors, especially in education and its reforms. The second chapter explored the implications for the Latin American reforms through the referential document "A New Public Management for Latin America", as a condition for the Region's development. This process was favored by the centrality in the categories of total quality, governability, accountability, and managerialism, all allied to the decentralizing State from the neoliberal point of view. The third chapter, as a more evident result, points to the organization of the broad education quality evaluation system, with emphasis on the Basic Education Evaluation System (SAEB), the IDEB, and the discourse on quality and equity, as supporting accountability categories. The emphasis is on the analysis of evaluation under the aegis of international events held by CLAD, considering how this Center considers evaluation practices, meritocracy, quality, and equity. In addition, how educators can be resilient in evaluation practices despite the current situation.